2020
DOI: 10.1016/j.bone.2019.115109
|View full text |Cite
|
Sign up to set email alerts
|

No pain, no gain? The effects of pain-promoting neuropeptides and neurotrophins on fracture healing

Abstract: Neuropeptides and neurotrophins are key regulators of peripheral nociceptive nerves and contribute to the induction, sensitization, and maintenance of pain. It is now known that these peptides also regulate non-neuronal tissues, including bone. Here, we review the effects of numerous neuropeptides and neurotrophins on fracture healing. The neuropeptides calcitonin-gene related peptide (CGRP), substance P (SP), vasoactive intestinal peptide (VIP), and pituitary adenylate cyclase-activating peptide (PACAP) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 162 publications
1
60
0
Order By: Relevance
“…Most notably, we find NGF and TrkA are localized predominantly at the chondro-osseous transition zone, where cartilage undergoes hypertrophy and transforms to bone adjacent to the invading vasculature 6,15 . Our genetic models of endogenous NGF and TrkA localization support previous studies observing peak expression of neurotrophins and their receptors during the hypertrophic cartilage phase of repair [47][48][49] . While our mRNA expression data show a peak at day 10, possible delays in mRNA-to-protein synthesis were considered when harvesting samples at day 14 for histological analysis.…”
Section: Discussionsupporting
confidence: 86%
“…Most notably, we find NGF and TrkA are localized predominantly at the chondro-osseous transition zone, where cartilage undergoes hypertrophy and transforms to bone adjacent to the invading vasculature 6,15 . Our genetic models of endogenous NGF and TrkA localization support previous studies observing peak expression of neurotrophins and their receptors during the hypertrophic cartilage phase of repair [47][48][49] . While our mRNA expression data show a peak at day 10, possible delays in mRNA-to-protein synthesis were considered when harvesting samples at day 14 for histological analysis.…”
Section: Discussionsupporting
confidence: 86%
“…42 Not only NGF, but also BDNF, play a key regulatory part of pain in the periphery. 43 Ion channel genes such as TRPV1, Nav1.3 and Nav1.7, are also investigated in RA pain. Synthesized in DRGs, TRPV1 is linked to inflammatory pain and peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to fracture and CGRP, as recently summarized [6], several investigators have shown CGRP expression at the fracture site and reported correlative findings. Prior to the studies reported in this issue of EBioMedicine by Appelt et al [1] perhaps the best evidence Contents lists available at ScienceDirect EBioMedicine journal homepage: www.elsevier.com/locate/ebiom for a role of CGRP in fracture repair was a report that intraperitoneal injection with CGRP inhibitor significantly impaired fracture healing in a rat model, as demonstrated by a significant reduction in mineralized callus with an increase in cartilage [9].…”
mentioning
confidence: 92%
“…With regard to fracture and CGRP, as recently summarized [6] , several investigators have shown CGRP expression at the fracture site and reported correlative findings. Prior to the studies reported in this issue of EBioMedicine by Appelt et al.…”
mentioning
confidence: 92%
See 1 more Smart Citation